THE MALE LECTURERS TALK TOWARD THE FEMALE STUDENTS LEARNING MOTIVATION IN EFL CLASSROOM - Pratiwi, Findy Elsa; Sahib, Rahmawansyah; Zulihi, Zulihi; Maulidil Mursyid, Andi Miftahul (English Language Education Study Program, 2023)
The male lecturers talk toward the female students' learning motivation shows that lecturers talks by male lecturers have a very significant impact on the learning motivation of female students. This study aims to examine the types of lecturers talk used by male lecturers based on Flanders theory using FIAC (Flanders Interaction Analysis Categories) and their impact on female students' learning motivation. This study used a descriptive qualitative design, were collected data through observation and interviews. The instruments used in the observations were video recordings for three observation class meetings and the instruments used in the interviews were audio recordings. The result showed that from 7 types of lecturers talk, 6 types appeared. The type most often used by male English lecturers is the gives information. Meanwhile, the impact of lecturers talk on the learning motivation of female students is more likely to have an impact on the extrinsic motivation of students in the classroom such as, the desire to study the material voluntarily, be responsible, and good relations with lecturers. Thus, this study is expected to be references by which lecturers could consider the types of lecturers talk to be implemented to improve their students' motivation and interest during the classroom.